2022
DOI: 10.1007/s00432-022-04532-x
|View full text |Cite
|
Sign up to set email alerts
|

Monalizumab efficacy correlates with HLA-E surface expression and NK cell activity in head and neck squamous carcinoma cell lines

Abstract: PurposeNKG2A, an inhibitory receptor expressed on NK cells and T cells, leads to immune evasion by binding to HLA-E expressed on cancer cells. Here, we investigated the relationship between HLA-E surface expression on head and neck squamous cell carcinoma (HNSCC) cell lines and the e cacy of monalizumab, an NKG2A inhibitor, in promoting NK cell activity. MethodsSix HNSCC cell lines were used as target cells. After exposure to IFN-γ, HLA-E surface expression on HNSCC cell lines was measured by ow cytometry. Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
2
0
1
Order By: Relevance
“…The activity of mononuclear cells may play a significant role in this process 41 . Studies indicate that B cells may participate in immune surveillance by producing antibodies, and B cells could represent a promising new direction for HNSCC therapy, allowing HNSCC patients to benefit from an immunotherapeutic perspective 42 . Research on Monalizumab primarily focuses on the treatment of solid tumors, including HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of mononuclear cells may play a significant role in this process 41 . Studies indicate that B cells may participate in immune surveillance by producing antibodies, and B cells could represent a promising new direction for HNSCC therapy, allowing HNSCC patients to benefit from an immunotherapeutic perspective 42 . Research on Monalizumab primarily focuses on the treatment of solid tumors, including HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Such treatment has, thus far, shown a tolerable safety profile in humans (Andre et al , 2018 ; Tinker et al , 2019 ; Borst et al , 2020 ; Galot et al , 2021 ; Herbst et al , 2022 ). It has been demonstrated that monalizumab's efficacy strongly depends on HLA‐E expression on tumor cells (Lee et al , 2022 ). However, when used as a monotherapy, monalizumab has not shown evidence for meaningful clinical activity that, by contrast, has been substantiated when combined with durvalumab (Herbst et al , 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Po otro lado, los melanocitos expresan en la superficie celular y secretan la molécula HLA-E (Derré et al, 2006). Aún que la expresión de la molécula HLA-G haya sido mucho estudiada en tumores espinocelulares de otras localizaciones, como cabeza y cuello (Lee et al, 2023) y en tumores ginecológics (Boujelbene et al, 2019), no hay estudios sobre HLA-E en los espinocelulares cutáneos. De la misma forma, no hay estudios sobre la molécula HLA-E en carcinomas basocelulares.…”
Section: Hla-eunclassified